2015
DOI: 10.1007/s10719-015-9577-7
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acids: biomarkers in endocrinal cancers

Abstract: Sialylations are post translational modification of proteins and lipids that play important role in recognition, signaling, immunological response and cell-cell interaction. Improper sialylations due to altered sialyl transferases, sialidases, gene structure and expression, sialic acid metabolism however lead to diseases and thus sialic acids form an important biomarker in disease. In the endocrinal biology such improper sialylations including altered expression of sialylated moieties have been shown to be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Sialic acids are negatively charged nine-carbon carboxylated monosaccharides on glycosylated proteins and lipids formed due to post translational modification [ 9 ]. Most cell surface glycans are highly sialylated and often involved in cell-cell and/or cell-extracellular matrix interaction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sialic acids are negatively charged nine-carbon carboxylated monosaccharides on glycosylated proteins and lipids formed due to post translational modification [ 9 ]. Most cell surface glycans are highly sialylated and often involved in cell-cell and/or cell-extracellular matrix interaction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Li et al [ 21 ], found that the combined determination of SA with hydroxyproline provides a better diagnosis value than either CA-125 or HE4. S. Ghosh [ 22 ] discusses in a recent work, how SA in serum may also be used as a clinical predictor for Ovarium cancer. Finally, we add that Thakkar et al [ 23 ] found that protein-bound sialic acid (PBSA) provides the highest overall ability to discriminate between ovarian cancer patients and healthy subjects, in comparison with other glycoproteins in serum [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[37] Aberrant expression of sialic acids is closely associated with invasive and metastatic cancer. [77,78] Ta rgeting sialic acids is a promising strategy to suppress tumor motility and metastasis. An ovel fluorinated sialic acid analogue( P-3Fax-Neu5Ac, 18) was shown to deplete a-2,3-/a-2,6-linked sialic acids, thereby blockingt he synthesis of sialoglycan in murine melanoma and ultimately diminishing the migratory capacity of cancerc ells.…”
Section: Cancermentioning
confidence: 99%
“…Aberrant expression of sialic acids is closely associated with invasive and metastatic cancer . Targeting sialic acids is a promising strategy to suppress tumor motility and metastasis.…”
Section: Targeting Properties Of Mono‐ and Disaccharidesmentioning
confidence: 99%